Faculty Members’ Perception of the Efficacy of Active Learning Strategies in Open and Distance Learning Environment in Bangladesh Open University - Bhuiyan, Md. Omar Faruk (PJDOL, 2025)
This study aims to assess the efficacy of active learning strategies within the context of open and distance learning (ODL), considering that most participants are adults. To investigate the practical implementation of active learning in the Open and Distance Learning (ODL) setting, two research questions have been formulated regarding the research issue. The research employed a mixed-methods strategy. Data were gathered from faculty members via survey questionnaires and comprehensive interviews. One hundred and two educators completed the questionnaire in the study. Convenience sampling was utilized to choose five faculty members for in-depth interviews. Active learning strategies are crucial and efficacious instructional methods within the ODL framework. These tactics promote engagement and connection among students, and between students and educators. Among the 18 identified active learning strategies, only few have been frequently utilized in contemporary classrooms. Fifty percent of the active learning procedures are deployed intermittently, while the other strategies are infrequently or never used. The faculty members' responses indicate that students express satisfaction with the active learning approaches utilized in the classroom. The study results recommended to integrate active learning and student-centred instruction inside the ODL framework.